Poverty Dynamics in Turkey: A Multinomial Logit Model - Çakmak Şahin, Senem; Kılıç, İbrahim Engin (Ekonomika, 2021)
The availability of longitudinal data allows researchers to analyse the dynamics of poverty. By using the Turkish Statistical Institute’s (TurkStat) Income and Living Conditions Survey micro dataset, we analyse the households’ long-term monetary poverty conditions. We categorise poverty as transitory and chronic and employ the multinomial logit method to analyse determinants of each types of poverty. Results indicate that education and household size are the most effective factors for reducing transitory poverty, and for chronic poverty, the most effective factors are having a regular job and having a skilled occupation; insurance, home ownership, and number of children are important determinants for both types of poverty.
Keywords: poverty dynamics; chronic poverty; transitory poverty; multinomial logit